Cover Picture: Werner Reutter: A Visionary Pioneer in Molecular Glycobiology (ChemBioChem 13/2017). (26th June 2017) - Hinderlich, Stephan; Tauber, Rudolf; Bertozzi, Carolyn R.; Hackenberger, Christian P. R.
Abstract : The cover picture shows the late Prof. Dr. Werner Reutter to whom this special issue of ChemBioChem is dedicated. Prof. Reutter was one of the most influential glycobiologists of his time and made numerous contributions to molecular and chemical biology as well as to medicinal research. Several of his major discoveries are highlighted on this cover image, for example his studies ond ‐galactosamine metabolism as well as the elucidation of key enzymatic steps in sialic acid biosynthesis including the epimerization of UDP‐ N ‐acetylglucosamine and the phosphorylation of N ‐acetylmannosamine by the bifunctional enzyme GNE. Finally, he contributed to the field of metabolic glycoengineering by showing that N‐acylated mannosamines can be transformed to the corresponding sialic acids on cell surfaces and to the identification of carbohydrate‐based inhibitors that block sialic acid biosynthesis. Cover image Jad Bou Reslan based on a photo kindly provided by Anja Reutter. More information can be found in the Editorial by C. P. R. Hackenberger et al. onpage 1279 in Issue 13, 2017 (DOI:10.1002/cbic.201700277 ).